Hand function limitations and the influence on toothbrushing efficacy and plaque control - Shanni Aurelia; Tiarma Talenta Theresia; Ria Hayuningtyas (Dentika: Dental Journal, 2026)
Maintaining healthy teeth and periodontal tissues is strongly dependent on effective oral hygiene, but physical act of toothbrushing can be significantly hindered by limitations in hand function. Issues such as diminished handgrip strength, joint stiffness, persistent pain, and reduced manual dexterity often make thorough cleaning a challenge. Therefore, this literature review aimed to evaluate how the specific hand function limitations impact general toothbrushing efficacy and plaque control. Data were collected from PubMed and Google Scholar for analysis on English and Indonesian articles published over the past decade. The compiled evidence showed that poor handgrip strength and limited dexterity directly correlated with heavier plaque accumulation, increased risks of periodontitis, and compromised oral self-care habits. These challenges were particularly prevalent among older populations and individuals managing musculoskeletal or systemic conditions such as rheumatoid arthritis. Recognizing hand function limitations as a critical determinant of oral health showed the urgent need for more adaptive, customized oral hygiene strategies.